Understanding violence: the intertwining of morality, religion, capitalism and violence: a philosophical stance - Magnani, Lorenzo (Studies in Applied Philosophy, Epistemology and Rational Ethics Series, 2024)
This book offers a philosophical account of violence, engaged with both empirical and theoretical debates in disciplines such as cognitive science, sociology, psychiatry, anthropology, political theory, evolutionary biology, and theology.The primary thesis is that violence is intertwined with morality and typically enacted for "moral" reasons.